Student and Faculty View of Learning with Technology : Implications for Teaching. - Komarek, Jenna (My University, 2009)
This poster reports the results of a survey distributed via email to all student and faculty on campus during the 2007 semester. The survey was designed to gather student and faculty ratings related to preferred ways of learning new technologies, beliefs about learning, and expectations for use of technology in teaching.
Color poster with text and graphs describing research conducted by Jenna Komarek, advised by Linda J. Campenter.
Keywords: Educational technology; College students--Attitudes; College teachers--Attitudes; Posters